The Beaver Hills country : a history of land and life - MacDonald, Graham, 1944- (AU Press, 2009)
This book explores a relatively small but interesting and unusual region of Alberta between the North Saskatchewan and the Battle Rivers. The Beaver hills arose where mountain glaciers from the west met continental ice-sheets from the east to create a complex and diverse landscape. MacDonald relates how climate, water levels, wildlife, vegetation, and fire have shaped the possibilities and provided the challenges to the people who have called the region home.